Penyuluhan Dan Pendampingan Karakter Anak Melalui Keterampilan Berbahasa Anak Panti Asuhan Ashabil Rayyan - Dwi Mutia Chan; Zuraida Khairani; Najmi Hayati; Novi Fitriani; Susanti Marisya; Olin Nita (Kilau Publishing, 2026)
Character education for children in orphanages faces specific challenges due to limited personal mentoring and lack of external stimulation. One crucial aspect that can serve as a means for character building is language skills. This Community Service (PkM) activity aims to provide counseling and assistance for children's character building through the optimization of language skills for foster children at the Ashabil Rayyan Orphanage, Padang. The implementation method consisted of three main stages: preparation (initial observation and problem mapping), execution (educational lectures, language skills workshops, storytelling simulations, and role-playing), and evaluation through assessing participants' attitudes and verbal communication skills. The target audience for this activity was orphanage children ranging from elementary to secondary school ages. The results of the activity showed a significant increase in children's awareness in applying polite, disciplined, and honest language ethics in daily life. In addition, speaking skills and the participants' courage in expressing themselves and their opinions in public improved. This activity is concluded to be effective in integrating positive character values into children's language skills, thereby fostering individuals who are more confident, well-mannered, and communicative in their social environment